Pens versus syringes to deliver insulin among elderly patients with type 2 diabetes: a randomized controlled clinical trial - Rafael Vaz Machry; Gustavo Fonseca Cipriani; Henrique Umpierre Pedroso; Rafaela Ramos Nunes; Thayme Luisa Souza Pires; Raquel Ferreira; Betina Vescovi; Gabriela Pereira de Moura; Ticiana Costa Rodrigues (Diabetology & Metabolic Syndrome, 2021)
Abstract Background Diabetes mellitus (DM) is a prevalent disease among elderly population. As the disease progresses, insulin may become necessary. The use of pens application seems to be more practical. However, the influence of this method on glycemic control needs to be defined in elderly people. Methods Randomized clinical trial comparing pens and syringes for insulin application among patients with type 2 DM over 60 years old and Glycated Hemoglobin > 8.5% at baseline. The follow-up was 24 weeks, with monthly medical visits to adjust the treatment. All patients received insulin NPH and, if necessary, insulin Regular. We assessed glycemic control, adherence to treatment, hypoglycemia occurrence, need for adjustment in treatment and impact on quality of life, Results We included 121 patients with mean age of 65.75 years. Sixty-one were randomized for pen group (PG) and 60 patients for syringe group (SG). At baseline, mean HbA1c was 10.34 ± 1.66% and 9.90 ± 1.25% (p = 0.103) in PG and SG respectively. Mean HbA1c was 8.39 ± 1.28% in PG and 8.85 ± 1.74% in SG (p = 0.101) at 24 weeks. However, there was a more significant reduction in PG (− 1.94 ± 1.93% in PG and − 1.04 ± 1.46% in SG, p < 0.05) during follow-up. We found no difference in treatment adherence rates, hypoglycemia, greater need for insulin doses or oral medication, and progression to basal-bolus insulin scheme. We also found no difference in the impact of the disease on quality of life between groups. Conclusion Although we did not find any difference in the impact on quality of life, frequency of hypoglycemia or adherence, the PG showed a reduction in HbA1c higher in 24 weeks of follow-up. Clinical trial registration: NCT02517242